Cold Deck : A Novel - Barnes, H. Lee, 1944- (Book collections on Project MUSE., 2013)
Jude Helms is a Las Vegas casino dealer who barely survived the deadly MGM fire in 1980. More than two decades later, he's still dealing, a tired middle-aged man, divorced, struggling with debt, and trying to be a good father to his children. Then he loses his job, and his car is totaled in an accident. When an attractive woman friend offers to hep him get another job, Jude is happy to go along. Gradually, he realizes that his new job is part of an elaborate scheme to cheat a casino and that his own survival and that of his children depend on his finding the courage and ingenuity to extricate himself.--front jacket flap.